2009
DOI: 10.2146/ajhp080451
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an insulin therapy protocol: Applying the Baldrige approach

Abstract: The Baldrige approach was successfully used to implement a standard insulin therapy protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…15 Similar positive results have been reported for insulin order sets, blood culture order sets and acute myocardial infarction order sets. [16][17][18] A 2009 study showed that the adoption of an admission order set for community-acquired pneumonia led to a reduction of in-hospital and 30-day mortality by nearly 33% and had a favourable estimate of cost-effectiveness. 19 We present the first study of an admission order set for patients with liver disease and GI haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similar positive results have been reported for insulin order sets, blood culture order sets and acute myocardial infarction order sets. [16][17][18] A 2009 study showed that the adoption of an admission order set for community-acquired pneumonia led to a reduction of in-hospital and 30-day mortality by nearly 33% and had a favourable estimate of cost-effectiveness. 19 We present the first study of an admission order set for patients with liver disease and GI haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was defined as blood pressure more than 130/85 mmHg or use of any antihypertensive medication (Victor and Kaplan, 2008). DM was defined by a physician's diagnosis, a fasting plasma glucose level of ≥126 mg dL −1 or use of diabetic medications (Foster and Pitts, 2009). Echocardiography was done for all patients during their hospital stay by one cardiologist.…”
Section: Subjectsmentioning
confidence: 99%
“…1, 18, 20, 21, 2326, 34, 4052 Donihi et al described a decrease in insulin prescribing errors and adverse events 1 year after the implementation of a standardized protocol and order set for sliding scale insulin. 40 Through the implementation of these interventions, they report a significant decrease in prescribing errors and a decrease in hyperglycemia with no significant change in incidence of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…1, 18, 2023, 4042 Two groups specifically analyzed the impact of a committee focused on hypoglycemia and diabetes safety. Pasala et al described the impact of a hypoglycemia committee to decrease hypoglycemic events.…”
Section: Discussionmentioning
confidence: 99%